Transforming social policy in Europe? The EC's parental leave directive and misfit in the 15 member states - Gerda Falkner; Miriam Hartlapp; Simone Leiber; Oliver Treib (Max Planck Institute for the Study of Societies, 2002)
This paper presents first results from a collaborative research project which analyzes the national transposition, enforcement and application of six European labor law Directives in all 15 member states. Looking at the case of the EC's parental leave Directive (1996), it draws conclusions about the domestic impact of European social policy standards. It will interest practitioners as much as labor law experts that, in fact, adaptational pressure was created in all 15 member states. Although the overall economic impact of the Directive in terms of costs was rather modest, every single country had to change its rules. While misfit was rather small in Finland, France, Germany, Portugal, Spain and Sweden, the other member states were confronted with significant adaptation pressure. Political theorists may be surprised that our results cast doubts on the theoretical usefulness of focusing too much on matches or mismatches between European policies and domestic structures. We show that a very low degree of misfit may sometimes even be a problem rather than a condition for success and that the existence of considerable adaptational pressure may under certain conditions even be conducive to smooth implementation. In addition, several member states not only eliminated the misfit created by the Directive, but raised their domestic standards above the European minimum requirements. – – Dieses Papier stellt erste Ergebnisse eines Projektverbundes vor, der die rechtliche Umsetzung, administrative Durchführung und praktische Anwendung von sechs arbeitsrechtlichen EG-Richtlinien in allen 15 Mitgliedstaaten untersucht. Anhand der Richtlinie zum Elternurlaub (1996) werden hier die Auswirkungen europäischer Sozialstandards auf der nationalen Ebene behandelt. Für Praktiker und Arbeitsrechtsexperten gleichermaßen interessant dürfte unser Befund sein, dass die Richtlinie tatsächlich in allen Mitgliedstaaten Anpassungen nötig machte. Obwohl die von der Richtlinie verursachten Kosten insgesamt eher gering waren, musste doch jedes Land seine Regulierungen ändern. Während die erforderlichen Reformen in Deutschland, Finnland, Frankreich, Portugal, Spanien und Schweden von eher begrenzter Tragweite waren, sahen sich die übrigen Mitgliedstaaten mit beträchtlichem Anpassungsbedarf konfrontiert. Theoretisch Interessierte werden feststellen, dass unsere Ergebnisse Zweifel daran erwecken, ob die im Rahmen der Prognose des Anpassungserfolges bislang gängige Orientierung an der Größe des verursachten Anpassungsbedarfes wirklich sinnvoll ist. Wir zeigen, dass sehr kleiner misfit manchmal die erfolgreiche Anpassung sogar behindern kann, und dass hoher Anpassungsbedarf unter bestimmten Bedingungen größeren Erfolg verspricht. Darüber hinaus haben mehrere Mitgliedstaaten im Zuge der Implementation nicht nur die notwendigen Anpassungen vorgenommen, sondern ihre nationalen Standards über das von der Richtlinie geforderte Maß hinaus verändert.
Keywords: 300